The Effectiveness Of Canva Application In Fun English Learning To Improve The Students’ English Vocabulary (An Experimental Study For Grade XI Of SMK Balekambang Jepara) - Elsa Febriyanti; Haryanto Haryanto (Journal on Education, 2024)
Canva application functions to revive students' enthusiasm for learning English, especially in mastering vocabulary, an application medium that is attractive, flexible, and easy to operate is also needed. This study aims to describe the effectiveness of Canva application in Fun English Learning to improve the student’s English vocabulary. The participants were eleventh graders of SMK Roudhotul Mubtadi'in Balekambang Jepara from two different study groups. Each study group consists of 22 female students. Researchers then divided them into two groups, namely experimental and control. The experimental group received an English vocabulary-assisted by Canva, while the control group used PowerPoint slides as learning media. This experimental research uses a pretest-posttest test for each group. Data analysis techniques include descriptive analysis techniques and ANCOVA. The table also shows that the effect of pretest F(1,43) is 15.69, less than 0.05. The posttest effect F(1,43) was 1.422, less than 0.05, with an ETA squared of 0.03. The Fcount calculation result is 15.69 with df = (1, 41), p-value = 0.000 < 0.05. These results show differences in the average vocabulary of students who received media learning English using Canva compared to the control group.